Failure in Duty to Keep Rare Blood/Blood Donors ready before LSCS: A Case of Medical Negligence: NCDRC (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
NCDRC quoted in its judgment dated: 11.11.2021: “There is something about losing a mother that is permanent and inexpressible – a wound that will never quite heal.” – Susan Wiggs. NCDRC further added that we understand how challenging and painful a Mother’s Day without mom. The duties of the doctors to the patient are elaborated by the Hon’ble Supreme Court in the case of Dr. Laxman Balkrishan Joshi Vs. Dr. Trimbak Bapu Godbole and Anr (AIR 1969 SC 128)2 observed that the practitioner must bring to his task a reasonable degree of skill and knowledge and must exercise a reasonable degree of care. Neither the very highest nor a very low degree of care and competence judged. In the light of the particular circumstances of each case is what the law requires. The above principle was again applied by Supreme Court in the case of A.S. Mittal and Ors. vs. State of U.P. and Ors. (AIR 1989 SC 1570).3 It observed “A mistake by a medical practitioner which no reasonably competent and a careful practitioner would have committed is a negligent one.” This Research Paper deals with reasons for holding doctor/hospital negligent in an alleged death after PPH, not able to transfuse blood timely and delay in referral as few of the reasons. NCDRC found deficiency in service /medical negligence on the part of Doctor/Hospital and enhanced in facts and circumstances of case.
Keywords: PPH; Cause of death; Referral; Expert opinion; Medical literature